The Influence of Job Satisfaction and Organizational Culture on Performance and Organizational Commitment in Regionally-Owned Enterprises (BUMD) in Bogor City - Agung Wibowo; Nancy Yusnita; Widodo Sunaryo (International Journal of Management and Economic Research (IJOMER), 2026)
This study aims to analyze the influence of Organizational Culture on Employee Performance and Commitment to the Organization with Job Satisfaction as an intervening variable in Regionally-Owned Enterprises (BUMD) in Bogor City, namely Perumda Pasar Pakuan Jaya and Perumda Air Minum Tirta Pakuan. The research approach used is quantitative with a survey method of 212 respondents selected using proportional stratified random sampling. Data were analyzed using path analysis techniques with the help of SmartPLS to test the direct and indirect effects between variables. The results show that Organizational Culture has a positive and significant effect on Job Satisfaction, Employee Performance, and Commitment to the Organization. Job Satisfaction also has a positive and significant effect on Employee Performance and Commitment to the Organization. In addition, Job Satisfaction is proven to partially mediate the relationship between Organizational Culture and Employee Performance and Commitment to the Organization. These findings indicate that improving a strong and conducive organizational culture can increase job satisfaction which ultimately has an impact on improving employee performance and commitment. This study provides an empirical contribution in the development of organizational behavior models in the BUMD sector and provides practical implications for management in formulating strategies to improve performance and strengthen employee commitment through managing organizational culture and job satisfaction.